Les institutions de marche en Afrique subsaharienne. (With English summary.) - Fafchamps, M (2005)
Based on my May 2005 presentation to the Societe canadienne de science economique, this article summarizes the content of my book devoted to market institutions in sub-Saharan Africa. Organized around the ideas of trust and information sharing, the article discusses concepts and empirical findings pertaining to the enforcement of contracts in Africa. I argue that the fear of losing valuable relationships is the dominant enforcement mechanism in markets for manufactures and agricultural products. Contrary to much of the theoretical emphasis on reputational contracting, coordinated collective exclusion of cheaters is unknown. But decentralized exclusion can arise if breach of contract is interpreted as a signal of impending bankruptcy. I discuss the circulation of information about type and behavior, which is fraught with incentive problems, and the role of networks in shaping market interaction.